Working Memory and Learning Difficulties: An Evidence-Based Study in a Public Primary School in Jakarta - Susi Rutmalem Bangun; Tjhin Wiguna; Raden Irawati Ismail; Fransiska Kaligis; Noorhana Setyawati Winarsih (International Journal of Child Development and Mental Health, 2019)
Working memory is the mechanism used for temporary storage during more complex task performance/activity. A child’s learning ability is highly influenced by intelligence and memory. The deficit in working memory is one of the significant risks affecting a child’s learning capacity and causing learning difficulties. The objectives of this study were: trying to identify the proportion of children with learning difficulties, deficits in working memory and elaborating the relationship between them. This was a cross-sectional design study that was done in one public primary school in Jakarta involving 184 students from grades one to six. Working memory was assessed and based on the Indonesian version of Working Memory Rating Scale (WMRS), which was filled out by the class teachers. Learning difficulties are defined as conditions marked by the students’ achievements below the average academic class scores in one previous term. Chi-Square analysis is applied to find out the association, by using SPSS program for Windows. The study results showed that 87 (47.28%) children had learning difficulties with 11.41% (21 students) of them showing deficits in working memory. Children with working memory deficits had 4.826 times higher risk of learning difficulties compared to children without working memory deficits. Odds ratio was also significant (p<0.05) in the relationship between working memory deficits and learning difficulties in Indonesian literature (OR= 3.373), Mathematics (OR=4.935), and Science (OR=3.075). In conclusion, early detection for working memory deficits in primary students is a must, especially in inclusive primary schools, to prevent further learning difficulties.